2007
DOI: 10.1017/s0030605307004036
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, status and conservation of the bats of the Fiji Islands

Abstract: The poorly studied bat fauna of the Fiji Islands is of notable conservation importance because it includes one endemic species, several near endemics, and the best global populations of several threatened species. In addition, some of the species play a keystone role as pollinators and seed dispersers in valuable forest ecosystems. We visited 30 islands of the archipelago to survey bats and assess their conservation status and the potential threats to their continued existence. The Vulnerable Notopteris macdon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 37 publications
3
36
1
Order By: Relevance
“…The genus Pteropus (the ''flying foxes'') is represented by a diverse complement of species in eastern Melanesia, Micronesia, and Polynesia (extending as far east as the Cook Islands). Also occurring in the region are two older generic lineages endemic to the remote Pacific-Notopteris (two species of blossom bats, known from the modern faunas of New Caledonia, Vanuatu, and Fiji, as well as the subfossil record of Tonga) and Mirimiri (one species of ''monkeyfaced bat'', recorded only from montane forests on the island of Taveuni in Fiji) (Hill and Beckon, 1978;Flannery, 1995;Parnaby, 2002b;Helgen, 2005;Palmeirim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Pteropus (the ''flying foxes'') is represented by a diverse complement of species in eastern Melanesia, Micronesia, and Polynesia (extending as far east as the Cook Islands). Also occurring in the region are two older generic lineages endemic to the remote Pacific-Notopteris (two species of blossom bats, known from the modern faunas of New Caledonia, Vanuatu, and Fiji, as well as the subfossil record of Tonga) and Mirimiri (one species of ''monkeyfaced bat'', recorded only from montane forests on the island of Taveuni in Fiji) (Hill and Beckon, 1978;Flannery, 1995;Parnaby, 2002b;Helgen, 2005;Palmeirim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…At Nakanacagi cave we estimated c. 2,000 C. bregullae, with similar numbers in 2010 and 2011. Palmeirim et al (2005) reported native forest nearby, but we found the cave within disturbed forest, with agricultural land use and a timber mill nearby. We found nets and poles in the cave.…”
Section: Resultsmentioning
confidence: 70%
“…Neither was this species found in any cave or coastal overhang on Vanua Levu. Furthermore, the most important cave colony, recorded by Palmeirim et al (2007) on Yaqeta Island, was deserted and there was no evidence of recent use by bats (odour, fresh guano). The vandalized cave is located within a small fragment of forest frequented by goats (Plate 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations